THE TOLAKI CALENDAR SYSTEM FOR DETERMINING GOOD AND BAD DAYS - Ridhayanti, Nurul Resky (Al-Hilal: Journal of Islamic Astronomy, 2023)
The Tolaki people continue to base their way of life on traditions like the Tolaki calendar for identifying good and bad days. The Tolaki tribe employs a tool that is often employed as a weather forecast or as a guide for the community to carry out certain actions to ascertain this. The formulation of the issue is brought up by the author, who asks questions like: How does the Tolaki calendar system work?, How are the good and bad days for the Tolaki people determined?, and How is astronomical research related to the Tolaki calendar system?. The Tolaki Culture Book, which is processed with journals linked to the Tolaki Tribal Calendar System, is used in this research technique, which is a library method. It is studied descriptively and presented qualitatively. These are the study's findings: The moon's position in the night sky is used as the basis for the Tolaki calendar. The meanings of the names of the days in the month are used by the Tolaki people to identify good and bad days, and they use Naga Hari, Kutika, and Bilangari to ascertain the precise day and hour. The Tolaki calendar is identical to the Hijri calendar in astronomy since it uses a lunar calendar that keeps track of the moon's orbit. The Tolaki community uses the concept of good days and bad days as a guide for carrying out activities, but it cannot be utilized as a model for how to do Islamic devotion.